TERT Alterations Predict Tumor Progression in De Novo High-Grade Meningiomas Following Adjuvant Radiotherapy - Deng, Jiaojiao; Sun, Shuchen; Chen, Jiawei; Wang, Daijun; Cheng, Haixia; Chen, Hong; Xie, Qing; Hua, Lingyang; Gong, Ye (Frontiers in Oncology, 2021)
Background: Adjuvant radiotherapy (RT) is one of the most commonly used treatments for de novo high-grade meningiomas (HGMs) after surgery, but genetic determinants of clinical benefit are poorly characterized. Objective: We describe efforts to integrate clinical genomics to discover predictive biomarkers that would inform adjuvant treatment decisions in de novo HGMs. Methods: We undertook a retrospective analysis of 37 patients with de novo HGMs following RT. Clinical hybrid capture-based sequencing assay covering 184 genes was performed in all cases. Associations between tumor clinical/genomic characteristics and RT response were assessed. Overall survival (OS) and progression-free survival (PFS) curves were plotted using the Kaplan-Meier method. Results: Among the 172 HGMs from a single institution, 42 cases (37 WHO grade 2 meningiomas and 5 WHO grade 3 meningiomas) were identified as de novo HGMs following RT. Only TERT mutations (62.5% C228T; 25% C250T; 12.5% CN amp.) were significantly associated with tumor progression after postoperative RT (adjusted p=0.003). Potential different somatic interactions between TERT and other tested genes were not identified. Furthermore, TERT alterations (TERT-alt) were the predictor of tumor progression (Fisher’s exact tests, p=0.003), and was associated with decreased PFS (log-rank test, p=0.0114) in de novo HGMs after RT. Conclusion: Our findings suggest that genotyping for TERT-alt could help selection of patients who are likely to benefit from adjuvant RT after resection of newly diagnosed HGMs.